Virtual Labs for Postsecondary General Education and Applied Science Courses: Faculty Perceptions - Chudaeva, Elena; Soliman, Latifa (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2024)
General education science courses at a Canadian postsecondary institution implemented Beyond Labz virtual science labs. Faculty members teaching vocational science-related courses tested this resource. This qualitative study explores faculty member and learner perceptions of the efficacy of these virtual labs in terms of ease of use, designing hands-on activities, student engagement, and accessibility. Data are collected via a focus group, surveys, meetings, and interview notes. The study found that learners and faculty members may have different perceptions of the importance of virtual labs for the development of various skills. From the data, five themes emerge related to addressing the needs of diverse learners and utilizing multiple affordances of virtual labs. Although science virtual labs are perceived as a useful tool for teaching and learning science, faculty members identify barriers such as the need to develop digital literacy skills and initial training and institutional support when introducing new tools. Recommendations for effective science virtual labs curriculum integration are included.